Adiponectin oligomers as potential indicators of adipose tissue improvement in obese subjects - De Rosa, Anna; Monaco, Maria Ludovica; Capasso, Mario; Forestieri, Pietro; Pilone, Vincenzo; Nardelli, Carmela; Buono, Pasqualina; Daniele, Aurora (European journal of endocrinology, 2013)
ObjectiveAdiponectin is an adipocytokine that exerts beneficial effects on obesity and related disorders by two receptors (ADIPORs). Adiponectin is produced as a monomer that circulates in serum as different oligomers. The oligomerization state and the tissue expression of adiponectin and ADIPORs are linked to its biological activities. In this study, the levels of total adiponectin and its oligomers were evaluated in relation to obesity and surgical weight loss. The expression of adiponectin and ADIPORs was analyzed in visceral and subcutaneous adipose tissues of obese patients.Design and methodsIn 25 obese patients and 44 age- and sex-matched controls, the serum levels of adiponectin and its oligomers were measured and compared by ELISA, western blotting, and gel filtration. The expression of adiponectin and ADIPORs in both adipose tissues was evaluated by real-time quantitative PCR and western blotting.ResultsThe amount of each adiponectin oligomer, including the monomer, increases after weight loss. The reduced circulating levels of adiponectin and its oligomers are not associated with the adipose tissue depot-specific expression of adiponectin and ADIPORs.ConclusionsOur results suggest that in patients, adiposity is associated with the serum concentrations of adiponectin and its oligomers but not with adipose tissue depot-specific expression of adiponectin and ADIPORs. In particular, the increase in adiponectin monomer levels could probably be related to the improvement of the whole-body energy metabolism then being involved in the improvement of adipose tissue function after weight loss. This work indicates the importance of assessing the whole adiponectin oligomeric profile as further potential indicators of adipose tissue functions in obesity.